Demographic trends and disparities among NIH-funded medical school faculty in the US, 1970–2022 - Alyssa Browne (PLoS ONE, 2025)
Background Although gender and racial/ethnic trends and disparities are well documented among recipients of National Institutes of Health (NIH) research grant funding, little is known about the demographic trends and disparities within a critical subpopulation: NIH-funded medical school faculty. Methods This paper analyzes a rich dataset of full-time medical school faculty and their NIH grants from 1970 to 2022 and examines temporal trends in the demographic distribution and relative representation (representation index) of NIH-funded medical school faculty by gender, race/ethnicity, and their intersections. Results This paper reports that, while the gender gap in NIH funding has narrowed, a gender gap remains, particularly among highly funded faculty. Further, trends disaggregated by both gender and race/ethnicity demonstrate the particularly low relative representation of Black and Hispanic NIH-funded faculty, specifically Black and Hispanic women, that persists over time. Notably, although Asian men and women are represented at similar rates among medical school faculty overall, a gender gap in favor of Asian men has become more pronounced over time among NIH-funded Asian faculty. Conclusions Although there are efforts to recognize a broader set of metrics for a successful research career, research grant funding remains key for establishing research independence, tenure, and promotion. Thus, our findings of ongoing disparities underscore the urgent need to identify effective strategies to advance gender and racial/ethnic equity within NIH-funded medical school faculty.